Varicella Pneumonia in Young Adult Male: A Case Report - Uprety, Augraj; Pantha, Srijan; Gurung, Kum Bahadur; Aryal, Prakash; Timsina, Anup; Mandal, Dipesh; Yadav, Krishna Chandra; Shah, Nensi; Yadav, Dipendra; Pandey, Prajwal; et al. (Nepalese Respiratory Journal, 2024)
Varicella infection is a common disease in pediatric age group but is uncommon in adult. Varicella pneumonia is the dreaded complication in these patients leading to mortality, which is more pronounced in adult patients. This is a case report of a young adult male, presenting with Varicella pneumonia in severe hypoxic respiratory failure, which was successfully managed with oxygen therapy, acyclovir, and steroids.